1998
DOI: 10.1159/000029298
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Nebulized Salbutamol on Resting Energy Expenditure in Patients with Chronic Obstructive Pulmonary Disease and in Healthy Subjects

Abstract: This study investigated the contribution of a single dose of salbutamol by nebulizer to the increased resting energy expenditure (REE) frequently found in patients with chronic obstructive pulmonary disease (COPD) (n = 22), in comparison with a younger (n = 15) and an older healthy (n = 10) control group. The rise in REE after nebulization of 5 mg salbutamol was significantly higher in younger (11.4%) compared to older healthy subjects (5.7%; p < 0.05) and patients with COPD (4.2%; p < 0.001), which also accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…This was not the case with ipratropium bromide, an anticholinergic bronchodilator, or placebo. A similar finding was found by Creutzberg et al (23) who found an increase in BMR of 4 % after nebulization of 5 mg salbutamol. Congleton and Muers (20), however, did not find any change in BMR in 17 patients with COPD after eight months of 5 mg salbutamol per day.…”
Section: Medicationsupporting
confidence: 89%
See 3 more Smart Citations
“…This was not the case with ipratropium bromide, an anticholinergic bronchodilator, or placebo. A similar finding was found by Creutzberg et al (23) who found an increase in BMR of 4 % after nebulization of 5 mg salbutamol. Congleton and Muers (20), however, did not find any change in BMR in 17 patients with COPD after eight months of 5 mg salbutamol per day.…”
Section: Medicationsupporting
confidence: 89%
“…Body composition results were presented as FFMI as recommended by Vanltallie et al (23). It is important that techniques for body composition analysis are standardized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was based on the finding of a 5% increase in REE after inhaling 5 mg salbutamol in patients with COPD 28. Another study showed a positive correlation between 24-hour total energy expenditure and the daily dose of inhaled β-2-agonists 29.…”
Section: Discussionmentioning
confidence: 99%